2019
DOI: 10.1088/1742-6596/1237/2/022122
|View full text |Cite
|
Sign up to set email alerts
|

Research and analysis of threshold segmentation algorithms in image processing

Abstract: Image segmentation is one of the most difficult and important tasks in digital image processing. The accuracy and effect of segmentation determine the final success or failure of the calculation and analysis process. Therefore, analysis and improvement on basic image segmentation algorithms should be paid attention to in a quite wide range of applications. This paper mainly introduces and studies the principle and characteristics of threshold segmentation algorithm, and analyses the application scenarios of gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 5 publications
0
13
0
3
Order By: Relevance
“…Paper [8] investigated the main characteristics and principle of operation of the method of global threshold segmentation and the method of adaptive local threshold segmentation. It was found that for images with uneven lighting it is better to use the method of adaptive local threshold segmentation.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 3 more Smart Citations
“…Paper [8] investigated the main characteristics and principle of operation of the method of global threshold segmentation and the method of adaptive local threshold segmentation. It was found that for images with uneven lighting it is better to use the method of adaptive local threshold segmentation.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…It was found that for images with uneven lighting it is better to use the method of adaptive local threshold segmentation. The advantage of [8] is the ease of implementation of the methods. The disadvantage of [8] is the impossibility of determining the threshold for segmentation on high-contrast and complexly structured images.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…Combined with the characteristics of the existing threshold segmentation algorithm and feature recognition method. 12,13 The method used in this paper is local adaptive threshold segmentation. The segmentation method is that the image is divided into several small regions, and the gray value of each region corresponds to different features.…”
Section: Introductionmentioning
confidence: 99%